2021
DOI: 10.36706/jlso.10.1.2021.546
|View full text |Cite
|
Sign up to set email alerts
|

Performance of New Superior Variety of Rice and its Feasibility in Rainfed Rice Lowland of South Sumatra

Abstract: Rainfed lowland has great potential to produce rice in South Sumatra Province. Rice cultivation in such marginal lowland needs technological innovation for sustainable use. This study aimed to analyze the crop performance and farming feasibility of a New Superior Variety (VUB) in rainfed rice cultivation. The study was carried out on 2019/2020 in Tugu Jaya Village, Lempuing District, OKI Regency. It was implemented in a demonstration plot of rice cultivation covering 2 hectares, using Inpari 30 and 43 varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…When compared with the actual price of grain (Rp 4,000), rice cultivation with the implementation of Panca Kelola Ramah Lingkungan technology is feasible. Maryana et al (2021) reported that the higher the difference between the actual production and the production breakeven point, as well as the higher the difference between selling price and the break-even point, the greater the income received by farmers.…”
Section: Analysis On the Feasibility Of Rice Cultivationmentioning
confidence: 99%
“…When compared with the actual price of grain (Rp 4,000), rice cultivation with the implementation of Panca Kelola Ramah Lingkungan technology is feasible. Maryana et al (2021) reported that the higher the difference between the actual production and the production breakeven point, as well as the higher the difference between selling price and the break-even point, the greater the income received by farmers.…”
Section: Analysis On the Feasibility Of Rice Cultivationmentioning
confidence: 99%